2021
DOI: 10.1371/journal.pone.0244534
|View full text |Cite
|
Sign up to set email alerts
|

Predicting health behavior in response to the coronavirus disease (COVID-19): Worldwide survey results from early March 2020

Abstract: The current pandemic outbreak of the novel COVID-19, which originated from Wuhan in China in late 2019, has eventually spread to six continents with a rising toll of death cases. No vaccine has yet been developed for COVID-19. The compliance of the general public with the advice and regulations of the health authorities and the adoption of effective health behavior regimens are currently the only weapons to effectively cope with the disease. Here we report the results of a worldwide survey (n = 953) conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 26 publications
6
34
1
2
Order By: Relevance
“…Our findings are aligned with [15] who found older and more educated adults had higher risk perceptions compared to young and less-educated adults. In addition, we find that risk perception is significantly concentrated among the higher income groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are aligned with [15] who found older and more educated adults had higher risk perceptions compared to young and less-educated adults. In addition, we find that risk perception is significantly concentrated among the higher income groups.…”
Section: Discussionsupporting
confidence: 89%
“…Literature on behavioural response to Covid-19 is fast emerging [13][14][15][16][17][18]. The limitations highlighted in the context of the pandemic literature prior to Covid-19 holds true for the more recent studies as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies have revealed a relationship between fear and COVID-19 prevention behaviors (e.g., Chang et al, 2020 ; Harper et al, 2020 ; Anaki and Sergay, 2021 ). For example, Harper et al’s (2020) study revealed that people who are more fearful about COVID-19 engage more with the recommended preventive health behaviors such as regular hand washing and social distancing practices.…”
Section: Discussionmentioning
confidence: 99%
“…In some countries, citizens seem to follow social isolation and lockdown rules more readily than elsewhere. For example, Anaki and Sergay’s (2021) research found that people in the United States and Europe reportedly adopted less COVID-19 related precautionary behaviors than people in Asia. Current and future research on this situation will also provide significant benefits to these and similar struggles faced by today’s national and international authorities in tackling the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation